A Modified Double-Integral-Sliding-Mode-Controller for a Microgrid System With Uncertainty - Pradhan, Swati Sucharita; Pradhan, Raseswari (Distributed Generation & Alternative Energy Journal, 2020)
Recently infiltration of large scale of microgrid systems into the power grid is recorded. Among these systems, photovoltaic (PV) based microgrid systems are more in demand due to its renewable, pollution free properties and abundantly available fuel. Grid integration of this microgrid system again enhanced its energy efficiency. But, dynamics of this PV based microgrid system is highly nonlinear and uncertain in nature. It suffers from para- metric uncertainties. This kind of system can’t be controlled properly by conventional linear controllers. Sliding mode controller (SMC) is capable of controlling this kind of system with ease. However, SMC suffers from its inherent chattering introduction in the system output waveform. To reduce the chattering from the output waveform, there is requirement of some modifica- tion in the existing SMC structure dynamics. This paper presents an extended state observer based double integral sliding mode controller (DISMC) for this studied system. By using DISMC, the chattering magnitude is diminished greatly. Parameter uncertainties of the system lead to some unknown control states. These unknown states are identified by the state observer. Therefore, the proposed controller is more efficient in reference tracking, disturbance rejection and robust stability. To test the efficacies of the proposed controller, results of the studied system with this controller are compared with that of H∞ controller.